2009
DOI: 10.4067/s0718-58392009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Somatic Embryos and Zygotic Embryos for Obtaining Artificial Seeds of Rauli-Beech (Nothofagus alpina (Poepp. & Endl.) Oerst.)

Abstract: Somatic and zygotic embryos from mature seeds of rauli-beech, Nothofagus alpina (Poepp. & Endl.) Oerst., were encapsulated in different artificial endosperms in order to generate a cover that fulfills the function of nourishment and protection of the embryos, facilitating their later germination. The content of sodium alginate varied by 4%, 3%, and 2%, as did the immersion time in calcium chloride (CaCl2), which acts as complexing agent. The artificial endosperm components of the Murashige and Skoog medium (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
1
10
0
3
Order By: Relevance
“…Cartes et al [35] reported that the encapsulated somatic and zygotic Rauli-Beech (Nothofagus alpine) embryos had the same germination habits, which depended on the type of encapsulation applied, and they mentioned that the germination level of zygotic embryos was higher in comparison to somatic embryos. An automatic production and encapsulation artificial seeds protocol was established by [9].…”
Section: Somatic Embryosmentioning
confidence: 99%
See 4 more Smart Citations
“…Cartes et al [35] reported that the encapsulated somatic and zygotic Rauli-Beech (Nothofagus alpine) embryos had the same germination habits, which depended on the type of encapsulation applied, and they mentioned that the germination level of zygotic embryos was higher in comparison to somatic embryos. An automatic production and encapsulation artificial seeds protocol was established by [9].…”
Section: Somatic Embryosmentioning
confidence: 99%
“…On the other hand, some authors consider that the degree of vigour or maturity of the embryos at the moment of being encapsulated can influence the germination of encapsulated somatic embryos (ESEs) [63,64], cited in [35]. It was also suggested that encapsulation can affect embryo respiration (Redenbaugh, 1990) and this in turn might influence the germination and viability of somatic embryos [65].…”
Section: Somatic Embryosmentioning
confidence: 99%
See 3 more Smart Citations